Increased Performance of Thermoplastic Packaging Materials by Using a Mild Oxidizing Biobased Additive - Ferdinand Männle; Jens Kjær Jørgensen; Bjørn Steinar Tanem (International Journal of Polymer Science)
Green additives such as prodegradants based on natural fatty acids and iron can improve the environmental profile of thermoplastic packaging materials. We present two studies in which this is demonstrated. In the first study, the addition of a green prodegradant to a 5-layer gas barrier laminate during processing provided a laminate with significantly reduced oxygen transmission due to the resulting oxygen-consuming degradation process. The result shows that material reduction and cost efficiency of packaging laminates can be combined, since 5-layer laminates with reduced oxygen barrier layer thickness and retained gas barrier properties are feasible. The products are interesting from an ecological and economic aspect. In the second study, the addition of a green prodegradant to several qualities of polypropylene that are used in packaging applications leads to materials that are readily degraded in accelerated weathering. The molecular weight of the modified polypropylenes after 830 hours of accelerated weathering is reduced from typically 80.000 g/mole to 1.500–2.500 g/mole. At such molecular weight levels, digestion by microorganisms is feasible. The mild prodegradant used in the study does not lead to degradation during processing. Thermoplastics containing such additives are therefore fully recyclable provided that they have not been exposed to a long period of weathering.